Rationally engineered surface properties of carbon nanofibers for the enhanced supercapacitive performance of binary metal oxide nanosheets - Kim, Ji Hoon; Kim, Chang Hyo; Yoon, Hyeonseok; Youm, Je Sung; Jung, Yong Chae; Bunker, Christopher E.; Kim, Yoong Ahm; Yang, Kap Seung (ROYAL SOC CHEMISTRY, 2015)
The hybridization of an electrochemically active metal oxide with electrically conductive carbon nanofibers (CNFs) has been utilized as a solution to overcome the energy density limitation of carbon-based supercapacitors as well as the poor cyclic stability of metal oxides. Herein, we have demonstrated the growth of binary metal oxide nanosheets on the engineered surface of CNFs to fully exploit their electrochemical activity. Metal oxide nanosheets were observed to grow vertically from the surface of CNFs. The high structural toughness of the CNF-metal oxide composite under strong sonication indicated strong interfacial binding strength between the metal oxide and the CNFs. The rationally designed porous CNFs presented a high specific surface area and showed high capacity for adsorbing metal ions, where the active edge sites acted as anchoring sites for the nucleation of metal oxides, thereby leading to the formation of a well dispersed and thin layer structure of binary metal oxide nanosheets. Excellent electrochemical performance (e.g., specific capacitance of 2894.70 F g(-1) and energy density of 403.28 W h kg(-1)) was observed for these binary metal oxide nanosheets, which can be attributed to the large increase in the accessible surface area of the electrochemically active metal oxide nanosheets due to their homogeneous distribution on porous CNFs, as well as the efficient charge transfer from the metal oxide to the CNFs facilitated the improvement in the performance.
Keywords: ACTIVATED CARBON; NANOTUBES; CAPACITANCE; ADSORPTION; HYDROXIDES; COMPOSITE; NITROGEN; NICKEL; GROWTH; OXYGEN